Zig-Bee based Wireless Sensor Network for an Agricultural Environment - Sharma, Rahul (My University, 2014)
Wireless Sensor Networks underwent great technological advancements in the recent years, as a result of which, its use in monitoring and control of agricultural parameters became possible. Most of the improvements in agriculture technology and increase in the final yield was seen in the last ten years. As the farmers in most regions still rely on rainwater for crop irrigation, it is very important for them to closely monitor and control the distribution of water to crops in accordance with the uneven rainfall. The main reason for the suitability of wireless technology for irrigation is because of different weather conditions, soil composition and various crop types. Various aspects of agriculture must be thoroughly analyzed so as to make a correct choice of method. The accuracy of weather prediction is often poor, causing improper irrigation and then further leading to the losses on the part of the farmer. With the fast evolution of wireless sensor technologies and sensor devices, it has now become more feasible and economically viable to implement these for the monitoring and controlling of various parameters of agriculture for Precision Agriculture application. In this project a fully functional wireless sensor platform with Zig-bee and IEEE 802.15.4 modules have been developed directly without using any Controller. This includes design using Eagle, and implementation of Zig-Bee protocol stack, Application interfaces monitoring and control applications. Software stack is implemented after the hardware development is complete. The final stage is the development of test application.
M.E. (ECED)
Keywords: zigbee radios